Evaluation in pandemic times: meanings of learning in negotiation - Martins, Marcus Leonardo Bomfim (2021)
This article questions the effects of the pandemic context on the processes of meaning-making of the assessment-learning interface, perceived as an unavoidable element in the disputes over the meanings of a “democratic school”. Based on a discursive approach inscribed in the post-foundational agenda, normative documents that deal with education in the context of the Covid-19 pandemic, produced by the state Departments of Education in Rio de Janeiro and Minas Gerais, are explored. The analyses point to the hybridization of traditions and translations regarding the aforementioned interface, with intensified negotiation between meanings of learning from the perspective of acquiring something external to the learning subject, also as a particular response from that same subject.